EFEKTIFITAS PENERAPAN STRATEGI MANAJEMEN ACCOUNTING DAN STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN PANGSA PASAR DAN PROFITABILITAS (STUDI KASUS PT ARNOTT’S INDONESIA) - Baharuddin Saga (Universitas Pamulang, 2019)
Asia crisis in 1997 in 1997 infected many countries arround Asia, and many companies had to have an excelent corporate strategies in order for them to be survived in that tough situation. Those strategies should be continues strategies, which represented all value chain activities both primiry and supporting activities activities within the company. Than that value chain will be a competitive advantage and key success factor for the company because it is a blend of excellent strategies, which has an objective to achieve company goal and to be survived in crisis or in hard situation. PT Arnott Indonesia as subsidiary of multi national company, which is Arnott’s Australian Ltd, the pressure to be survived in biscuit industry is enormous. Thus, the company needs to have excellent strategies in each value chain activities and combine all those strategies into one corporate strategy that can be used to compete with all competitors within rhe biscuit industry. Management accounting and marketing strategies should be integrated and supported onewith each other.In additio,it has to be an activity that controlled all primary activities within Arnott’s Indonesia value chain. In conclusion this article isdisscussed about the role of management acoounting in PT arnott’s Indonesia in supporting company objectives and goals particulary activities thar are related with the marketing